Biological Contamination of Mars: Issues and Recommendations (The National Academies Press, 1992)

Mars Sample Return: Issues and Recommendations - National Research Council (The National Academies Press, 1997)
The Space Studies Board of the National Research Council (NRC) serves as the primary adviser to the National Aeronautics and Space Administration (NASA) on planetary protection policy, the purpose of which is to preserve conditions for future biological and organic exploration of planets and other solar system objects and to protect Earth and its biosphere from potential extraterrestrial sources of contamination. In October 1995 the NRC received a letter from NASA requesting that the Space Studies Board examine and provide advice on planetary protection issues related to possible sample-return missions to near-Earth solar system bodies.

Review of the MEPAG Report on Mars Special Regions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
Planetary protection is a guiding principle in the design of an interplanetary mission, aiming to prevent biological contamination of both the target celestial body and the Earth. The protection of high-priority science goals, the search for life and the understanding of the Martian organic environment may be compromised if Earth microbes carried by spacecraft are grown and spread on Mars. This has led to the definition of Special Regions on Mars where strict planetary protection measures have to be applied before a spacecraft can enter these areas. At NASA's request, the community-based Mars Exploration Program Analysis Group (MEPAG) established the Special Regions Science Analysis Group (SR-SAG2) in October 2013 to examine the quantitative definition of a Special Region and proposed modifications to it, as necessary, based upon the latest scientific results. Review of the MEPAG Report on Mars Special Regions reviews the conclusions and recommendations contained in MEPAG's SR-SAG2 report and assesses their consistency with current understanding of both the Martian environment and the physical and chemical limits for the survival and propagation of microbial and other life on Earth. This report provides recommendations for an update of the planetary protection requirements for Mars Special Regions.

Assessment of Planetary Protection Requirements for Mars Sample Return Missions - National Research Council (The National Academies Press, 2009)
NASA maintains a planetary protection policy to avoid the forward biological contamination of other worlds by terrestrial organisms, and back biological contamination of Earth from the return of extraterrestrial materials by spaceflight missions. Forward-contamination issues related to Mars missions were addressed in a 2006 National Research Council (NRC) book, Preventing the Forward Contamination of Mars. However, it has been more than 10 years since back-contamination issues were last examined. Driven by a renewed interest in Mars sample return missions, this book reviews, updates, and replaces the planetary protection conclusions and recommendations contained in the NRC's 1997 report Mars Sample Return: Issues and Recommendations. The specific issues addressed in this book include the following: The potential for living entities to be included in samples returned from Mars; Scientific investigations that should be conducted to reduce uncertainty in the above assessment; The potential for large-scale effects on Earth's environment by any returned entity released to the environment; Criteria for intentional sample release, taking note of current and anticipated regulatory frameworks; and The status of technological measures that could be taken on a mission to prevent the inadvertent release of a returned sample into Earth's biosphere.

The Quarantine and Certification of Martian Samples - National Research Council (The National Academies Press, 2002)
One of the highest-priority activities in the planetary sciences identified in published reports of the Space Studies Board's Committee on Planetary and Lunar Exploration (COMPLEX) and in reports of other advisory groups is the collection and return of extraterrestrial samples to Earth for study in terrestrial laboratories. In response to recommendations made in such studies, NASA has initiated a vigorous program that will, within the next decade, collect samples from a variety of solar system environments. In particular the Mars Exploration Program is expected to launch spacecraft that are designed to collect samples of martian soil, rocks, and atmosphere and return them to Earth, perhaps as early as 2015.International treaty obligations mandate that NASA conduct such a program in a manner that avoids the cross-contamination of both Earth and Mars. The Space Studies Board's 1997 report Mars Sample Return: Issues and Recommendations examined many of the planetary-protection issues concerning the back contamination of Earth and concluded that, although the probability that martian samples will contain dangerous biota is small, it is not zero.1 Steps must be taken to protect Earth against the remote possibility of contamination by life forms that may have evolved on Mars. Similarly, the samples, collected at great expense, must be protected against contamination by terrestrial biota and other matter. Almost certainly, meeting these requirements will entail opening the sample-return container in an appropriate facility on Earth-presumably a BSL-4 laboratory-where testing, biosafety certification, and quarantine of the samples will be carried out before aliquots are released to the scientific community for study in existing laboratory facilities. The nature of the required quarantine facility, and the decisions required for disposition of samples once they are in it, were regarded as issues of sufficient importance and complexity to warrant a study by the Committee on Planetary and Lunar Exploration (COMPLEX) in isolation from other topics. (Previous studies have been much broader, including also consideration of the mission that collects samples on Mars and brings them to Earth, atmospheric entry, sample recovery, and transport to the quarantine facility.) The charge to COMPLEX stated that the central question to be addressed in this study is the following: What are the criteria that must be satisfied before martian samples can be released from a quarantine facility?

Assessment of Planetary Protection Requirements for Spacecraft Missions to Icy Solar System Bodies - National Research Council (The National Academies Press, 2012)
NASA's exploration of planets and satellites during the past 50 years has led to the discovery of traces of water ice throughout the solar system and prospects for large liquid water reservoirs beneath the frozen ICE shells of multiple satellites of the giant planets of the outer solar system. During the coming decades, NASA and other space agencies will send flybys, orbiters, subsurface probes, and, possibly, landers to these distant worlds in order to explore their geologic and chemical context. Because of their potential to harbor alien life, NASA will select missions that target the most habitable outer solar system objects. This strategy poses formidable challenges for mission planners who must balance the opportunity for exploration with the risk of contamination by Earth's microbes, which could confuse the interpretation of data obtained from these objects. The 2000 NRC report Preventing the Forward Contamination of Europa provided a criterion that was adopted with prior recommendations from the Committee on Space Research of the International Council for Science. This current NRC report revisits and extends the findings and recommendations of the 2000 Europa report in light of recent advances in planetary and life sciences and, among other tasks, assesses the risk of contamination of icy bodies in the solar system.

Report Series: Committee on Planetary Protection: Evaluation of Bioburden Requirements for Mars Missions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Since the 1980s, national and international planetary protection policies have sought to avoid contamination by terrestrial organisms that could compromise future investigations regarding the origin or presence of Martian life. Over the last decade, the number of national space agencies planning, participating in, and undertaking missions to Mars has increased, and private-sector enterprises are engaged in activities designed to enable commercial missions to Mars. The nature of missions to Mars is also evolving to feature more diversity in purposes and technologies. As missions to Mars increase and diversify, national and international processes for developing planetary protection measures recognize the need to consider the interests of scientific discovery, commercial activity, and human exploration. The implications of these changes for planetary protection should be considered in the context of how much science has learned about Mars, and about terrestrial life, in recent years. At the request of NASA, this report identifies criteria for determining locations on Mars potentially suitable for landed robotic missions that satisfy less stringent bioburden requirements, which are intended to manage the risk of forward contamination.

Assessment of Planetary Protection Requirements for Venus Missions: Letter Report - National Research Council (The National Academies Press, 2006)
In 2005, the Planetary Protection Office of NASA asked the NRC to advise the Office on planetary protection concerns about missions to and from Venus. In particular, the NRC was asked to assess whether the surface and atmospheric environments of Venus might be capable of supporting microbial contamination from Earth, and, if so, to recommend prevention measures for future missions; to recommend planetary protection measures associated with return of samples from Venus to Earth; and to identify specific scientific investigations that may be needed to reduce any uncertainty in those assessments. This letter report provides a review of scientific considerations and past NRC studies on the issue; brief assessments of the key topics affecting the potential for forward and back contamination; a review of planetary protection considerations; and conclusions and recommendations.

Preventing the Forward Contamination of Mars - National Research Council (The National Academies Press, 2006)
Recent spacecraft and robotic probes to Mars have yielded data that are changing our understanding significantly about the possibility of existing or past life on that planet. Coupled with advances in biology and life-detection techniques, these developments place increasing importance on the need to protect Mars from contamination by Earth-borne organisms. To help with this effort, NASA requested that the NRC examine existing planetary protection measures for Mars and recommend changes and further research to improve such measures. This report discusses policies, requirements, and techniques to protect Mars from organisms originating on Earth that could interfere with scientific investigations. It provides recommendations on cleanliness and biological burden levels of Mars-bound spacecraft, methods to reach those levels, and research to reduce uncertainties in preventing forward contamination of Mars.

Preventing the Forward Contamination of Europa (The National Academies Press, 2000)

Evaluating the Biological Potential in Samples Returned from Planetary Satellites and Small Solar System Bodies: Framework for Decision Making - National Research Council (The National Academies Press, 1998)
For the first time since the Apollo program, NASA and space agencies abroad have plans to bring samples to Earth from elsewhere in the solar system. There are missions in various stages of definition to gather material over the next decade from Mars, an asteroid, comets, the satellites of Jupiter, and the interplanetary dust. Some of these targets, most especially Jupiter's satellites Europa and Ganymede, now appear to have the potential for harboring living organisms. This book considers the possibility that life may have originated or existed on a body from which a sample might be taken and the possibility that life still exists on the body either in active form or in a form that could be reactivated. It also addresses the potential hazard to terrestrial ecosystems from extraterrestrial life if it exists in a returned sample. Released at the time of the Internationl Committee on Space Research General Assembly, the book has already established the basis for plans for small body sample retruns in the international space research community.

Letter Report: Scientific Assessment of Options for the Disposition of the Galileo Spacecraft - National Research Council (The National Academies Press, 2000)

Review and Assessment of Planetary Protection Policy Development Processes - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Protecting Earth's environment and other solar system bodies from harmful contamination has been an important principle throughout the history of space exploration. For decades, the scientific, political, and economic conditions of space exploration converged in ways that contributed to effective development and implementation of planetary protection policies at national and international levels. However, the future of space exploration faces serious challenges to the development and implementation of planetary protection policy. The most disruptive changes are associated with (1) sample return from, and human missions to, Mars; and (2) missions to those bodies in the outer solar system possessing water oceans beneath their icy surfaces. Review and Assessment of Planetary Protection Policy Development Processes addresses the implications of changes in the complexion of solar system exploration as they apply to the process of developing planetary protection policy. Specifically, this report examines the history of planetary protection policy, assesses the current policy development process, and recommends actions to improve the policy development process in the future.

Planetary Protection Classification of Sample Return Missions from the Martian Moons - National Academies of Sciences, Engineering,; Medicine
An international consensus policy to prevent the biological cross-contamination of planetary bodies exists and is maintained by the Committee on Space Research (COSPAR) of the International Council for Science, which is consultative to the United Nations Committee on the Peaceful Uses of Outer Space. Currently, COSPAR's planetary protection policy does not specify the status of sample-return missions from Phobos or Deimos, the moons of Mars. Although the moons themselves are not considered potential habitats for life or of intrinsic relevance to prebiotic chemical evolution, recent studies indicate that a significant amount of material recently ejected from Mars could be present on the surface of Phobos and, to a lesser extent, Deimos. This report reviews recent theoretical, experimental, and modeling research on the environments and physical conditions encountered by Mars ejecta during certain processes. It recommends whether missions returning samples from Phobos and\/or Deimos should be classified as \

Planetary Protection Considerations for Missions to Solar System Small Bodies: Report Series—Committee on Planetary Protection - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The ultimate goal of planetary protection for outbound missions is to prevent harmful contamination that would inhibit future measurements designed to search for evidence of the existence or evolution of extraterrestrial life. Preventing harmful contamination is achieved by following specific guidelines based on existing scientific knowledge about the destination and the type of mission. This report responds to NASA's request for a study on planetary protection categorization of missions to small bodies, including whether there are particular populations of small bodies for which contamination of one object in the population would not be likely to have a tangible effect on the opportunities for scientific investigation using other objects in the population. In addressing NASA's request, the authoring committee considered surface composition of target bodies and their importance for prebiotic chemistry, along with size of the small-body populations, the current state of knowledge on the types of objects, the likelihood of a future scientific mission returning to any specific object, active object surface processes, and the size.